Teachers’questioning Strategies to Scaffold Students’ Learning in Reading - Anisah, Nur; Wuli Fitriati, Sri; Rukmini, Dwi (Universitas Negeri Semarang, 2019)
The objectives of this study are to analyze the type of teachers’ questioning strategies to scaffold students’ learning in reading, to analyze the students’ responses to answer the teachers’ questions, to analyze teachers’ questioning strategies in order to explain how the questions scaffold students’ learning in reading. The instruments used are classrooms observasion, teachers’ interviews, and document analysis. This study uses descriptive qualitative approach: a case study in Nasima Junior High School by means of questioning strategies proposed by Wragg and Brown (2001). The data are taken from classroom interaction of three teachers and sixty two students in three classes in nine meetings.The study shows that the teachers used all variant of key tactic questions. The most frequent strategy is listening to replies and responding tactic. In the term of students’ responses, the mostly response is active response in pure English. In the case of teachers’ questioning strategies to scaffold students’ learning reading, structuring, pitching and putting clearly, and directing and distributing tactic frequently perfome in before reading activities. During reading activities, the teachers performe all variant of key tactic question to scaffold the students, exceptly pacing tactic was never applied. In after reading activities, teachers mostly play sequencing tactic and pitching and putting clearly tactic to scaffold students’ learning reading.